Model Bermain Paralel sebagai Media dalam Pengembangan Kreativitas Anak (Sebuah Analisis Metode Pembelajaran Agama Islam) - Khoirun Nida, Fatma Laili; Khusna, Nurul (THUFULA, 2015)
The purpose of this study was to determine and analyze the implementation of the model of learning to play parallel to the Islamic religion as a means of developing children’s creativity. Model selection played as a variable in this study is based on the reality that life is synonymous with the world of children playing while developing creativity is needed at an early age. The study was conducted in RA Tarbiyatul Kesambi Mejobo 2014/2015 school year by using an qualitative approach.The  findings of this study indicate that through the application of models to play parallel to learning Islam can become a vehicle for the development of children’s creativity in RA Tarbiyatul Kesambi Mejobo Kudus. This method also gives many conveniences for children to understand the material contained in the teaching of Islam in view of their very own interest in the instrument used games. Several factors play a role in the implementation of  this model include an atmosphere of learning, their situation that encourages responsibility and independence within the students, as well as the factors that are more personal than the child itself.